2023
DOI: 10.3390/jcm12020544
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of High Molecular Weight Hyaluronic Acid and Latanoprost Eyedrops on Tear Functions and Ocular Surface Status in C57/BL6 Mice

Abstract: Anti-glaucoma eye drop treatment often induces ocular surface problems, including dry eyes, and may be associated with poor medication compliance. This study aimed to investigate the effects of a novel high molecular weight hyaluronic acid and Latanoprost eye drop on intraocular pressure, as well as the tear function and ocular surface alterations in wild type mice, comparing the results with the mice receiving commercially available Latanoprost eye drops and mice receiving no treatment. The mice were divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…A previous trial on humans reflected more effective IOP lowering by LPvHiHA containing 20 µg/mL LP than by commercial eye drops containing 50 µg/mL LP [ 43 ]. The combination of more effective transport of the active ingredient into the AH with less ocular surface inflammation may explain this observation [ 20 ]. Our data suggest that LPvHiHA produces better LP transport to the AH than cLP and dLP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A previous trial on humans reflected more effective IOP lowering by LPvHiHA containing 20 µg/mL LP than by commercial eye drops containing 50 µg/mL LP [ 43 ]. The combination of more effective transport of the active ingredient into the AH with less ocular surface inflammation may explain this observation [ 20 ]. Our data suggest that LPvHiHA produces better LP transport to the AH than cLP and dLP.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that the delivery of LP in an eye drop with vHiHA (LPvHiHA) had favorable effects on ocular surface staining and tear functions [ 20 ]. Indeed, more recent data indicated that the ocular surface of wild-type (WT) mice receiving LPvHiHA eye drops over 7 days was in better health than that of mice receiving a commercial LP (cLP) eye drop.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations